A Cross-Linked Interconnecting Layer Enabling Reliable and Reproducible Solution-Processing of Organic Tandem Solar Cells - Liu, Chao; Du, Xiaoyan; Gao, Shuai; Classen, Andrej; Osvet, Andres; He, Yakun; Mayrhofer, Karl; Li, Ning; Brabec, Christoph (Advanced Energy Materials, 2020)
The performance of tandem organic solar cells (OSCs) is directly related to the functionality and reliability of the interconnecting layer (ICL). However, it is a challenge to develop a fully functional ICL for reliable and reproducible fabrication of solution-processed tandem OSCs with minimized optical and electrical losses, in particular for being compatible with various state-of-the-art photoactive materials. Although various ICLs have been developed to realize tandem OSCs with impressively high performance, their reliability, reproducibility, and generic applicability are rarely analyzed and reported so far, which restricts the progress and widespread adoption of tandem OSCs. In this work, a robust and fully functional ICL is developed by incorporating a hydrolyzed silane crosslinker, (3-glycidyloxypropyl)trimethoxysilane (GOPS), into poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS), and its functionality for reliable and reproducible fabrication of tandem OSCs based on various photoactive materials is validated. The cross-linked ICL can successfully protect the bottom active layer against penetration of high boiling point solvents during device fabrication, which widely broadens the solvent selection for processing photoactive materials with high quality and reliability, providing a great opportunity to continuously develop the tandem OSCs towards future large-scale production and commercialization.
CRIS-Team Scopus Importer:2020-02-25
Keywords: (3-glycidyloxypropyl)trimethoxysilane; cross-linking; interconnecting layer; organic tandem solar cells; solution-processing

Double-Cable Conjugated Polymers Based on Simple Non-Fused Electron Acceptors for Single-Component Organic Solar Cells - Liu, Baiqiao; Liang, Shijie; Karuthedath, Safakath; He, Yakun; Wang, Jing; Tan, Wen Liang; Li, Hao; Xu, Yunhua; Laquai, Frederic; Brabec, Christoph; Mcneill, Christopher R.; Xiao, Chengyi; et al. (Macromolecules, 2023)
In this work, a non-fused electron acceptor with near-infrared absorption was introduced into double-cable conjugated polymers for single-component organic solar cells (SCOSCs). The non-fused electron acceptor contains a simple thienyl-phenyl-thienyl core with 2-(3-oxo-2,3-dihydroinden-1ylidene)malononitrile (IC) as the end group, which was used as the side unit to create double-cable conjugated polymers. In addition, poly(benzodithiophene) was selected as the conjugated backbone, in which the number of chlorine (Cl) atoms was varied to tune the optical and electronic properties. The new double-cable polymers were successfully applied in SCOSCs, providing an efficiency of over 8% with a broad photoresponse from 300 to 800 nm. When the number of Cl atoms on the repeat unit was increased from 2 to 3, the open-circuit voltage was enhanced to 1.01 V, yielding a low voltage loss of 0.59 eV, while the efficiency was reduced to 5.28%. The reduced performance is explained by the increased charge recombination in this polymer, as observed by transient absorption spectroscopy. This work reports a set of IC-based NIR double-cable conjugated polymers, which inspire material design toward more efficient SCOSCs.
CRIS-Team WoS Importer:2023-02-24

Double-Cable Conjugated Polymers with Pendent Near-Infrared Electron Acceptors for Single-Component Organic Solar Cells - Liang, Shijie; Liu, Baiqiao; Karuthedath, Safakath; Wang, Jing; He, Yakun; Tan, Wen Liang; Li, Hao; Xu, Yunhua; Li, Ning; Hou, Jianhui; Tang, Zheng; Laquai, Frederic; et al. (Angewandte Chemie International Edition, 2022)
Double-cable conjugated polymers with near-infrared (NIR) electron acceptors are synthesized for use in single-component organic solar cells (SCOSCs). Through the development of a judicious synthetic pathway, the highly sensitive nature of the 2-(3-oxo-2,3-dihydroinden-1-ylidene)malononitrile (IC)-based electron acceptors in basic and protonic solvents is overcome. In addition, an asymmetric design motif is adopted to optimize the packing of donor and acceptor segments, enhancing charge separation efficiency. As such, the new double-cable polymers are successfully applied in SCOSCs, providing an efficiency of over 10 % with a broad photo response from 300 to 850 nm and exhibiting excellent thermal/light stability. These results demonstrate the powerful design of NIR-acceptor-based double-cable polymers and will enable SCOSCs to enter a new stage.
CRIS-Team WoS Importer:2022-07-29

Evidencing Excellent Thermal- and Photostability for Single-Component Organic Solar Cells with Inherently Built-In Microstructure - He, Yakun; Heumüller, Thomas; Lai, Wenbin; Feng, Guitao; Classen, Andrej; Du, Xiaoyan; Liu, Chao; Li, Weiwei; Li, Ning; Brabec, Christoph (Advanced Energy Materials, 2019)
Solution-processed organic solar cells (OSCs) are promising low-cost, flexible, portable renewable sources for future energy supply. The state-of-the-art OSCs are typically fabricated from a bulk-heterojunction (BHJ) active layer containing well-mixed donor and acceptor molecules in the nanometer regime. However, BHJ solar cells suffer from stability problems caused by the severe morphological changes upon thermal or illumination stress. In comparison, single-component organic solar cells (SCOSCs) based on a double-cable conjugated polymer with a covalently stabilized microstructure is suggested to be a key strategy for superior long-term stability. Here, the thermal- and photostability of SCOSCs based on a model double-cable polymer is systematically investigated. It is encouraging to find that under 90 °C & 1 sun illumination, the performance of SCOSCs remains substantially stable. Transport measurements show that charge generation and recombination (lifetime and recombination order) hardly change during the aging process. Particularly, the SCOSCs exhibit ultrahigh long-term thermal stability with 100% PCE remaining after heating at temperature up to 160 °C for over 400 h, indicating an excellent candidate for extremely rugged applicatio
Keywords: device stability; double-cable conjugated polymers; thermal- and photostability; organic photovoltaics; single-component organic solar cells

High performance tandem organic solar cells via a strongly infrared-absorbing narrow bandgap acceptor - Jia, Zhenrong; Qin, Shucheng; Meng, Lei; Ma, Qing; Angunawela, Indunil; Zhang, Jinyuan; Li, Xiaojun; He, Yakun; Lai, Wenbin; Li, Ning; Ade, Harald; Brabec, Christoph; et al. (Nature Communications, 2021)
Tandem organic solar cells are based on the device structure monolithically connecting two solar cells to broaden overall absorption spectrum and utilize the photon energy more efficiently. Herein, we demonstrate a simple strategy of inserting a double bond between the central core and end groups of the small molecule acceptor Y6 to extend its conjugation length and absorption range. As a result, a new narrow bandgap acceptor BTPV-4F was synthesized with an optical bandgap of 1.21 eV. The single-junction devices based on BTPV-4F as acceptor achieved a power conversion efficiency of over 13.4% with a high short-circuit current density of 28.9 mA cm−2. With adopting BTPV-4F as the rear cell acceptor material, the resulting tandem devices reached a high power conversion efficiency of over 16.4% with good photostability. The results indicate that BTPV-4F is an efficient infrared-absorbing narrow bandgap acceptor and has great potential to be applied into tandem organic solar cells.
CRIS-Team Scopus Importer:2021-01-15

Industrial viability of single-component organic solar cells - He, Yakun; Li, Ning; Heumüller, Thomas; Wortmann, Jonas; Hanisch, Benedict; Aubele, Anna; Lucas, Sebastian; Feng, Guitao; Jiang, Xudong; Li, Weiwei; Bäuerle, Peter; Brabec, Christoph (Joule, 2022)
Although the power conversion efficiencies (PCEs) of bulk heterojunction (BHJ) organic solar cells (OSCs) continue increasing toward the 20% milestone, important factors for industrial application are mostly neglected, such as photostability and cost potential. Single-component OSCs (SCOSCs) employing materials with chemically bonded donor and acceptor moieties successfully overcome the immiscibility between the donor and the acceptor as well as the resultant self-aggregation under external stress. To inspire a broader interest, the industrial figure of merit (i-FoM) of BHJ OSCs and the corresponding SCOSCs is calculated and analyzed, which includes PCE, photostability, and synthetic complexity (SC) index. Despite having a slightly more complex synthesis, all SCOSCs exhibit increased i-FoM values compared with the corresponding BHJ OSCs, and with the increase in efficiency, SCOSCs possess further potential for a higher i-FoM value. With the excellent photostability of nearly all investigated single-component semiconductors, SCOSCs are coming into the focus of attention for industrial utilization.
CRIS-Team Scopus Importer:2022-07-01
Keywords: i-FoM; industrial figure of merit; PCE; photostability; power conversion efficiency; SC index; SCOSCs; single-component organic solar cells; synthetic complexity index

Layer-by-layer processed binary all-polymer solar cells with efficiency over 16% enabled by finely optimized morphology - Zhang, Yue; Wu, Baoqi; He, Yakun; Deng, Wanyuan; Li, Jingwen; Li, Junyu; Qiao, Nan; Xing, Yifan; Yuan, Xiyue; Li, Ning; Brabec, Christoph; Wu, Hongbin; et al. (Nano Energy, 2022)
Optimal active layer morphology is a prerequisite for high-efficiency all-polymer solar cells (all-PSCs). Herein, we report that the vertical phase separation as well as microstructures of the polymer donor and acceptor can be finely optimized in layer-by-layer (LbL) processed all-PSCs. By using 1-chloronaphthalene as the solvent additive during the deposition of the polymer acceptor in the top layer and applying thermal annealing on the entire active layer, bulk-heterojunction like morphology with favorable vertical composition distribution, improved lamellar ordering of the polymer donor (PBDB-T), and the formation of polymer fibrils of the polymer acceptor (PYT) have been realized simultaneously. This favorable morphology led to greatly enhanced exciton splitting efficiency, reduced trap density, improved charge transport, and suppressed charge recombination loss. As a result, the LbL processed all-PSCs of PBDB-T/PYT afforded a power conversion efficiency (PCE) of 16.05%, which is one of the highest PCEs for binary all-PSCs. Moreover, a fill factor (FF) of 0.77 has been obtained, which is the highest value for all-PSCs based on polymerized small molecule acceptors up to date. This work demonstrates an effective strategy for morphology optimization of LbL processed all-PSCs, which will greatly contribute to efficiency breakthrough.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Active layer morphology; All-polymer solar cells; High-efficiency; Layer-by-layer processing; Vertical composition distribution

Molecular Donor–Acceptor Dyads for Efficient Single-Material Organic Solar Cells - Lucas, Sebastian; Kammerer, Jochen; Pfannmoeller, Martin; Schroeder, Rasmus R.; He, Yakun; Li, Ning; Brabec, Christoph; Leydecker, Tim; Samori, Paolo; Marszalek, Tomasz; Pisula, Wojchiech; Mena-Osteritz, Elena; et al. (Solar RRL, 2020)
Single-material organic solar cells (SMOSCs) promise several advantages with respect to prospective applications in printed large-area solar foils. Only one photoactive material has to be processed and the impressive thermal and photochemical long-term stability of the devices is achieved. Herein, a novel structural design of oligomeric donor–acceptor (D–A) dyads 1–3 is established, in which an oligothiophene donor and fullerene acceptor are covalently linked by a flexible spacer of variable length. Favorable optoelectronic, charge transport, and self-organization properties of the D–A dyads are the basis for reaching power conversion efficiencies up to 4.26% in SMOSCs. The dependence of photovoltaic and charge transport parameters in these ambipolar semiconductors on the specific molecular structure is investigated before and after post-treatment by solvent vapor annealing. The inner nanomorphology of the photoactive films of the dyads is analyzed with transmission electron microscopy (TEM) and grazing-incidence wide-angle X-ray scattering (GIWAXS). Combined theoretical calculations result in a lamellar supramolecular order of the dyads with a D–A phase separation smaller than 2 nm. The molecular design and the precise distance between donor and acceptor moieties ensure the fundamental physical processes operative in organic solar cells and provide stabilization of D–A interfaces.
CRIS-Team Scopus Importer:2020-12-04
Keywords: ambipolar charge transport; donor–acceptor dyads; fullerenes; oligothiophenes; single-material organic solar cells

Molecular-Level Hybridization of Nafion with Quantum Dots for Highly Enhanced Proton Conduction - Wu, Wenjia; Li, Yifan; Liu, Jindun; Wang, Jingtao; He, Yakun; Davey, Kenneth; Qiao, Shi-Zhang (Advanced Materials, 2018)
Nanophase-separated membranes hold promise for fast molecule or ion transfer. However, development and practical application are significantly hindered by both the difficulty of chemical modification and nanophase instability. This can be addressed by organic–inorganic hybridization of functional fillers with a precise distribution in specific nanophase. Here, a molecular-level hybridization for nanophase-separated Nafion using 2–5 nm quantum dots (QDs) as a new smart filler is demonstrated. Two kinds of QDs are prepared and used: hydrophilic polymer-like QDs (PQDs) and hydrophobic graphene oxide QDs (GQDs). Because of selective interactions, QDs offer advantages of matched structural size and automatic recognition with the nanophase. A distinctive synthesis of subordinate-assembly, in which QDs are driven by the self-assembly of Nafion affinity chains, is reported. This results in a precise distribution of QDs in the ionic, or backbone, nanophases of Nafion. The resulting PQDs in the ionic nanophase significantly increase membrane proton conduction and device output-power without loss of mechanical stability. This is difficult to realize with conventional fillers. The GQDs in the backbone nanophase reduce the crystallinity and significantly augment membrane water uptake and swelling capacities. © 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinhe
Keywords: molecule-level hybridization; nanophase-separated membrane; hydrogen fuel cell; proton conduction; quantum dots

Molecular Oligothiophene–Fullerene Dyad Reaching Over 5% Efficiency in Single-Material Organic Solar Cells - Aubele, Anna; He, Yakun; Kraus, Teresa; Li, Ning; Mena-Osteritz, Elena; Weitz, Paul; Heumüller, Thomas; Zhang, Kaicheng; Brabec, Christoph; Bäuerle, Peter (Advanced Materials, 2021)
A novel donor–acceptor dyad, 4, in which the conjugated oligothiophene donor is covalently connected to fullerene PC71BM by a flexible alkyl ester linker, is synthesized and applied as photoactive layer in solution-processed single-material organic solar cells (SMOSCs). Excellent photovoltaic performance, including a high short-circuit current density (JSC) of 13.56 mA cm−2, is achieved, leading to a power conversion efficiency of 5.34% in an inverted cell architecture, which is substantially increased compared to other molecular single materials. Furthermore, dyad 4-based SMOSCs display excellent stability maintaining 96% of the initial performance after 750 h (one month) of continuous illumination and operation under simulated AM 1.5G irradiation. These results will strengthen the rational molecular design to further develop SMOSCs for potential industrial application.
CRIS-Team Scopus Importer:2021-09-10
Keywords: charge transport; device performance; donor–acceptor dyads; long-term stability; single-material organic solar cells

Quantitative Analysis of Charge Dissociation by Selectively Characterizing Exciton Splitting Efficiencies in Single Component Materials - He, Yakun; Hanisch, Benedict; Osvet, Andres; Lüer, Larry; Aubele, Anna; Bäuerle, Peter; Li, Weiwei; Li, Ning; Brabec, Christoph (Israel Journal of Chemistry, 2021)
Exciton dissociation between donor and acceptor is the decisive process to determine the photovoltaic performance of organic solar cells (OSCs). The rather fast dynamics of photo-induced charge generation in well-optimized bulk heterojunction (BHJ) composites complicate the quantitative analysis of the charge generation efficiency for donor and acceptor units. Herein, we report time-resolved photoluminescence (TRPL) investigations and demonstrate their potential as a quantitative and contactless characterization technique allowing to separately determine the exciton splitting efficiency of donor and acceptor moieties in selected single component materials. We demonstrate that the exciton splitting efficiency for donor or acceptor moieties can be separately adjusted in these materials by post-treatment, while the corresponding BHJ composites undergo excessive phase separation upon external stress. By relating the separate exciton splitting efficiencies to their photovoltaic performance, the limiting factor in corresponding OSCs, either charge generation or recombination, is identified.
CRIS-Team Scopus Importer:2021-10-22
Keywords: charge dissociation; charge transfer; exciton splitting efficiency; organic solar cells; single component materials; transient photoluminescence

Revealing Hidden UV Instabilities in Organic Solar Cells by Correlating Device and Material Stability - Classen, Andrej; Heumüller, Thomas; Wabra, Isabell; Gerner, Johannes; He, Yakun; Einsiedler, Lukas; Li, Ning; Matt, Gebhard; Osvet, Andres; Du, Xiaoyan; Hirsch, Andreas; Brabec, Christoph (Advanced Energy Materials, 2019)
With state-of-the-art organic solar cells (OSCs) surpassing 16% efficiency, stability becomes critical for commercialization. In this work, the power of using photoluminescence (PL) measurements on plain films is demonstrated, as well as high-performance liquid chromatography analysis to reveal the origin of UV instabilities in OSCs based on the most commonly used acceptors PC70BM ([6,6]-phenyl-C71-butyric acid methyl ester), ITIC (3,9-bis(2-methylene-(3-(1,1-dicyanomethylene)-indanone))-5,5,11,11-tetrakis(4-hexylphenyl)-dithieno[2,3-d:2′,3′-d′]-s-indaceno[1,2-b:5,6-b′]dithiophene), and o-IDTBR (indacenodithiophene-based non-fullerene acceptor). The UV dependent stability tests reveal instabilities in solar cells based on PC70BM and ITIC while devices based on o-IDTBR are highly stable even under UV illumination. The analysis of solar cell devices based on charge extraction and sub-bandgap external quantum efficiency only shows the UV-dependent emergence of traps, while PL spectra of plain films on glass allows the disentanglement and identification of individual instabilities in multi-component bulk-heterojunction devices. In particular, the PL analysis demonstrates UV instabilities of PC70BM and ITIC toward the processing additive 1,8 diiodooctane (DIO). The chemical analysis reveals the in-depth mechanism, by providing direct proof of photochemical reactions of PC70BM and ITIC with UV-induced radicals of DIO. Based on this scientific understanding, it is shown how to stabilize PBQ-QF:PC70BM devices.
CRIS-Team Scopus Importer:2019-09-17
Keywords: degradation; diiodooctane; organic solar cells; stability; UV

Single-Component Organic Solar Cells with Competitive Performance - He, Yakun; Li, Ning; Brabec, Christoph (Organic Materials, 2021)
Organic semiconductors with chemically linked donor and acceptor units can realize charge carrier generation, dissociation and transport within one molecular architecture. These covalently bonded chemical structures enable single-component organic solar cells (SCOSCs) most recently to start showing specific advantages over binary or multi-component bulk heterojunction concepts due to simplified device fabrication and a dramatically improved microstructure stability. The organic semiconductors used in SCOSCs can be divided into polymeric materials, that is, double-cable polymers, di-block copolymers as well as donor–acceptor small molecules. The nature of donor and acceptor segments, the length and flexibility of the connecting linker and the resultant nanophase separation morphology are the levers which allow optimizing the photovoltaic performance of SCOSCs. While remaining at 1–2% for over a decade, efficiencies of SCOSCs have recently witnessed significant improvement to over 6% for several materials systems and to a record efficiency of 8.4%. In this mini-review, we summarize the recent progress in developing SCOSCs towards high efficiency and stability, and analyze the potential directions for pushing SCOSCs to the next efficiency milestone.
Keywords: double-cable polymers; di-block copolymers; donor–acceptor small molecules; single-component organic solar cells; photovoltaic performance; device stability

Structure and linkage assessment of T-shaped Pyrrolidine[60]Fullerene- and Isoxazoline[60]Fullerene-BODIPY-triarylamine hybrids - Rocha-Ortiz, Juan S.; Montalvo-Acosta, Joel José; He, Yakun; Insuasty, Alberto; Hirsch, Andreas; Brabec, Christoph; Ortiz, Alejandro (Dyes and Pigments, 2023)
Eight novel C60-BODIPY-Triarylamine electroactive triads have been synthesized and characterized. Using pyrrolidine (PIR and BDPF series) and isoxazoline (ISO series) as linkers between the fullerene and the BODIPY-Triarylamine (-TAA) system, the effect of these linkers along with different functionalization on the TAA on the electronic properties were studied. Moreover, their photophysical and electrochemical properties were investigated by comparing them to the reference substances BDP, 10a, 10b, and C60. All C60-BODIPY-TAA derivatives absorb visible light strongly in a range between 535 and 563 nm, and photoexcitation of the BODIPY unit causes photo-induced electron transfer, producing the corresponding charge-separated species, which was confirmed by solvatochromic effects on fluorescence measurements. The direction of charge transfer was also revealed by their redox potentials. A better electron affinity was observed for the ISO series when compared with PIR and BDPF. Thermogravimetric analysis showed that the pyrrolidine derivatives are more stable than their isoxazoline analogs and the insertion of alkoxy units in the triads triggers a better thermal endurance in the studied compounds.
CRIS-Team Scopus Importer:2023-06-30
Keywords: BODIPY dyes; Electron transfer; Isoxazoline[60]Fullerene; Pyrrolidine[60]Fullerene; Triarylamines

Tailoring the Nature of Interface States in Efficient and Stable Bilayer Organic Solar Cells by a Transfer-Printing Technique - Wang, Rong; Jiang, Youyu; Gruber, Wolfgang; He, Yakun; Wu, Mingjian; Weitz, Paul; Zhang, Kaicheng; Lüer, Larry; Forberich, Karen; Unruh, Tobias; Spiecker, Erdmann; Deibel, Carsten; et al. (Advanced Materials Interfaces, 2022)
Bulk heterojunction organic solar cells (BHJ-OSCs) are designed to overcome inefficient charge generation and limited exciton diffusion of organic semiconductors. However, there are some disadvantages involving inherent voltage losses, microstructure control, and operational instability. Bilayer solar cells (BL-OSCs) without mixed regions are free from these problems and offer a platform to explore the photophysical processes at the donor-acceptor interface. Here, a breakthrough for n-i-p BL-OSCs in charge generation efficiency is reported. A gradual adjustment of the molecular interface orientation of the polymer donor (PM6) is accompanied by the evolution of charge-transfer states and Forster energy transfer. Besides, less recombination losses and superior morphological stability of BL-OSCs are achieved at a PCE comparable to that of BHJ-OSCs with similar layer thickness. This investigation confirms the feasibility of manufacturing BL-OSCs by a transfer printing method and provides a versatile architecture to study fundamental interface phenomena in OSCs independent from microstructure disorder.
CRIS-Team WoS Importer:2022-04-29

Thermal-Driven Phase Separation of Double-Cable Polymers Enables Efficient Single-Component Organic Solar Cells - Feng, Guitao; Li, Junyu; He, Yakun; Zheng, Wenyu; Wang, Jing; Li, Cheng; Tang, Zheng; Osvet, Andres; Li, Ning; Brabec, Christoph; Yi, Yuanping; Yan, He; et al. (Joule, 2019)
Conventional organic solar cells (OSCs) need two components that function as donor and acceptor, respectively. Although there has been wishful thinking about constructing OSCs based on a single component, it is generally believed to be highly challenging to achieve efficient single-component OSCs (SCOSCs). In this work, we design a new double-cable conjugated polymer containing a strongly crystalline backbone as donor and aromatic side units as acceptor. With a high annealing temperature (230°C), both the backbones and perylene bisimide side units could self-organize into ordered nanostructures. This enables efficient charge transport and low charge recombination, resulting in a record efficiency of 6.3% in SCOSCs. The cells also exhibit excellent stability, with >90% efficiency retention over 300 h of continuous one-sun illumination. These results suggest that the concept of SCOSCs is highly promising, especially to overcome the limitations of conventional OSCs toward industrial application.
CRIS-Team Scopus Importer:2019-07-19
Keywords: conjugated polymers; double cable; nanophase separation; single-component organic solar cells; thermal driven

Ultrastable Single-component Material Devices: the Next Frontier for Organic Solar Cells - He, Yakun; Bäuerle, Peter; Li, Weiwei; Li, Ning; Brabec, Christoph (nanoGe, 2022)

Ultrastable single-component organic solar cells: the next frontier towards industrial viability - He, Yakun; Brabec, Christoph; Heumüller, Thomas; Wortmann, Jonas; Hanisch, Benedict; Aubele, Anna; Li, Ning; Feng, Guitao; Jiang, Xudong; Li, Weiwei; Bäuerle, Peter; Lucas, Sebastian (Proceedings of International Conference on Hybrid and Organic Photovoltaics (HOPV22), 2022)
Power conversion efficiencies (PCEs) of bulk heterojunction (BHJ) organic solar cells (OSCs) continue increasing towards the 20% milestone mainly due to the emerging non-fullerene acceptors (NFAs). While significant efforts have been devoted to efficiency analysis, important factors for industrial application are mostly neglected, such as photostability and the cost potential. Single-component organic solar cells (SCOSCs) employing materials with donor and acceptor moieties chemically bonded within one molecule or polymer, successfully overcome the immiscibility between donor and acceptor as well as the resultant self-aggregation under external stress [1]. To inspire a broader interest, in this work, the industrial figure of merit (i-FOM) of OSCs are calculated and analyzed, which includes PCE, photostability, and synthetic complexity (SC) index [2]. Based on the notable advantages of SCOSCs over the correspondent BHJ OSCs, especially the enhanced stability and simplified film processing, we systematically compare the i-FOM values of BHJ OSCs and the corresponding SCOSCs. SCMs exhibit overall much higher i-FOM values compared with the BHJ OSCs, and the highest value reaches 0.3, which is comparable with (or higher than) the ones of high-efficiency BHJ OSCs. With the increase of efficiency, SCOSCs possess the further potential to a higher i-FOM value. Among all factors, the synthetic complexity of SCOSCs is slightly higher than that of the corresponding BHJ OSCs due to the extra synthetic step for connecting donor and acceptor moieties. Nevertheless, the covalent bonding structure of SCMs helps overcome the immiscibility between D and A for proper nanophase separation and consequently a decent PCE, in comparison with the large-scale phase separation for the corresponding BHJ systems. More importantly, the higher i-FOM of SCOSCs is mostly ascribed to the substantially enhanced stability compared with BHJ [3]. SCOSCs based on dyad 1 exhibit surprisingly high photostability under concentrated light (7.5 suns and 30 suns), corresponding to an almost unchanged device stability up to ten thousand hours under 1-sun illumination. For realizing industrial application, SCOSCs have to give a high efficiency comparable to the current high-efficiency BHJ OSCs, while BHJ should be developed in the direction of less complicated synthesis. With joint efforts of researchers from multidiscipline, SCOSCs will see continuing progress in efficiency, reaching an i-FOM value enough for industrial application. <br

Ultra-stable single component organic solar cells under thermal and/or illumination pressure: the next superior organic photovoltaics? - He, Yakun; Baeuerle, Peter; Li, Weiwei; Heumüller, Thomas; Li, Ning; Brabec, Christoph (13th Conference on Hybrid and Organic Photovoltaics (HOPV21), 2021)
Stability issue is the core restriction for the application of organic solar cells (OSCs). However, state-of-the-art OSCs based on bulk-heterojunction concept suffer from stability problems caused by the severe morphological changes upon thermal or illumination stress [1]. Single-component concept, enabled by the covalently-bonded structure with donor and acceptor in one molecule, presents attractive advantages such as a simplification of device fabrication and a stabilization of microstructure [2]. Recently, with the rapid improvement of efficiency from 2-3% to 8.4% for single-component organic solar cells (SCOSCs), the reports on their stability however are scanty. In this work, we for the first time systematically investigated the stability under thermal and illumination stress of a series of SCOSCs based on polymeric (SCP3, PBDBPBI-Cl) and molecular (Dyad1, 2, 3, 4) materials. Under thermal pressure, double-cable polymer-based SCOSCs exhibited excellent thermal stability with no degradation at 90 oC for 3000 hours, partially attributed to the high temperatures (around 200 oC) for post-treating active layer during device fabrication. Such rather high annealing temperatures are plausible to create microstructure arrangements which are in thermodynamic equilibrium after cooling down. Furthermore, without precedent, we studied the thermal stability comparison among a series of SCOSCs based on D-A small molecules (Dyad1, 2 and 3) with the same donor and acceptor units but differently long alkyl space linkers. Since macroscopic diffusion of molecules is excluded in these dyads, the length of the spacer can only provide the necessary flexibility for sub-nm rearrangements caused by thermal stress. Interestingly, dyads showed a distinctly different behavior, Dyad1 with the shortest linker exhibiting the highest thermal stability, while Dyad3 with the longest linker showing the worst thermal stability [3]. This highlights the need for further in-depth studies on the dual importance of spacer length for performance and stability. Moreover, Dyad1-based SCOSCs exhibited extraordinary illumination stability, retaining 98% of the initial PCE under concentrated light equal to 7.5-suns for over 1000 hours, which could be among the highest illumination stability for solution-processed OSCs. Based on the outstanding stability, SCOSCs could be an ideal candidate to study the ultimate stability under extremely rugged accelerating conditions such as high temperature and concentrated light. Since the morphological evolution is excluded, SCOSCs could serve as a model system to selectively study interface degradation. In the near future, SCOSCs will see a prospective renaissance with 10% efficiency and 20 years lifetime for industrial applications.

Unraveling the Charge-Carrier Dynamics from the Femtosecond to the Microsecond Time Scale in Double-Cable Polymer-Based Single-Component Organic Solar Cells - He, Yakun; Wang, Bingzhe; Lüer, Larry; Feng, Guitao; Osvet, Andres; Heumüller, Thomas; Liu, Chao; Li, Weiwei; Guldi, Dirk Michael; Li, Ning; Brabec, Christoph (Advanced Energy Materials, 2021)
Single-component organic solar cells (SCOSCs) have witnessed great improvement during the last few years with the champion efficiency jumping from the previous 2-3% to currently 6-11% for the representative material classes. However, the photophysics in many of these materials has not been sufficiently investigated, lacking essential information regarding charge-carrier dynamics as a function of microstructure, which is highly demanded for a better understanding and potential guidance for further improvements. In this work, for the first time, the charge-carrier dynamics of a representative double-cable polymer, which achieves efficiencies of over 6% as an active layer in SCOSCs, is investigated across seven orders of magnitude in time scale, from fs-ps charge generation to ns-mu s charge recombination processes. Specific emphasis is placed on understanding the impact of thermal post-treatment on the charge dissociation and recombination dynamics. Annealing the photoactive layer at 230 degrees C results in the highest photovoltaic performance because of efficient charge generation in parallel to suppressed recombination. This work intends to present a complete picture of the charge-carrier dynamics in SCOSCs using the representative double-cable polymer PBDBPBI-Cl.
CRIS-Team WoS Importer:2021-12-31

Unraveling the Role of Non-Fullerene Acceptor with High Dielectric Constant in Organic Solar Cells - Zhang, Yue; He, Yakun; Zeng, Liang; Lüer, Larry; Deng, Wanyuan; Chen, Yuting; Zhou, Jiadong; Wang, Zhiqiang; Brabec, Christoph; Wu, Hongbin; Xie, Zengqi; Duan, Chunhui (Small, 2023)
Increasing the relative dielectric constant is a constant pursuit of organic semiconductors, but it often leads to multiple changes in device characteristics, hindering the establishment of a reliable relationship between dielectric constant and photovoltaic performance. Herein, a new non-fullerene acceptor named BTP-OE is reported by replacing the branched alkyl chains on Y6-BO with branched oligoethylene oxide chains. This replacement successfully increases the relative dielectric constant from 3.28 to 4.62. To surprise, BTP-OE offers consistently lower device performance relative to Y6-BO in organic solar cells (16.27% vs 17.44%) due to the losses in open-circuit voltage and fill factor. Further investigations unravel that BTP-OE has resulted in reduced electron mobility, increased trap density, enhanced first order recombination, and enlarged energetic disorder. These results demonstrate the complex relationship between dielectric constant and device performance, which provide valuable implications for the development of organic semiconductors with high dielectric constant for photovoltaic application.
CRIS-Team Scopus Importer:2023-05-26
Keywords: dielectric constant; energetic disorder; first order recombination; non-fullerene acceptors; organic solar cells

Utilizing the unique charge extraction properties of antimony tin oxide nanoparticles for efficient and stable organic photovoltaics - Liu, Chao; Félix, Roberto; Forberich, Karen; Du, Xiaoyan; Heumüller, Thomas; Matt, Gebhard; Gu, Ening; Wortmann, Jonas; Zhao, Yicheng; Cao, Yuanyuan; He, Yakun; Ying, Lei; et al. (Nano Energy, 2021)
Simultaneously enhancing device performance and longevity, as well as balancing the requirements on cost, scalability, and simplification of processing, is the goal of interface engineering of organic solar cells (OSCs). In our work, we strategically introduce antimony (Sb3+) cations into an efficient and generic n-type SnO2 nanoparticles (NPs) host during the scalable flame spray pyrolysis synthesis. Accordingly, a significant switch of conduction property from an n-type character to a p-type character is observed, with a corresponding shift in the work function (WF) from 4.01 ± 0.02 eV for pristine SnO2 NPs to 5.28 ± 0.02 eV for SnO2 NPs with 20 mol. % Sb content (ATO). Both pristine SnO2 and ATO NPs with fine-tuned optoelectronic properties exhibit remarkable charge carrier extraction properties, excellent UV resistance and photo-stability being compatible with various state-of-the-art OSCs systems. The reliable and scalable pristine SnO2 and ATO NPs processed by doctor-blading in air demand no complex post-treatment. Our work offers a simple but unique approach to accelerate the development of advanced interfacial materials, which could circumvent the major existing interfacial problems in solution-processed OSCs.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Antimony doped tin oxide; Doping mechanism; Interface engineering; Metal oxide nanoparticles; Organic photovoltaics